PENGENALAN TEKNOLOGI AUGMENTED REALITY UNTUK PENINGKATAN KUALITAS PEMBELAJARAN PADA PPTQ AZZAKIYYAH - Rudy Cahyadi; Budi Suyanto; Andi Nurkholis; Andrey Ferriyan; Yuli Fauziah (CV. Denasya Smart Publisher, 2026)
This Community Service activity aims to improve the understanding of teachers, ustadz, and ustadzah regarding the concept, working principles, and potential use of Augmented Reality as an interesting, interactive, and character-appropriate learning medium for students in Islamic boarding schools. The main problem faced by partners is the low basic understanding of Augmented Reality among educators and the absence of specific activities that systematically introduce Augmented Reality in the learning context. As a solution, the Community Service team developed an introductory program that explains the basic concepts of Augmented Reality, examples of its application in education, and opportunities for its adaptation to religious and general materials at PPTQ Azzakiyyah. The activity, which was carried out on December 17, 2025, was considered successful; participants stated that their understanding and insight into Augmented Reality increased, the material was clear and relevant, and the level of satisfaction was in the very good category. The results of the questionnaire showed that all aspects of the assessment were in the good category, so that this Community Service was effective in increasing the empowerment of partners in literacy and initial readiness to utilize Augmented Reality as a learning support. This program also opens up insights that AR can be integrated selectively without abandoning Islamic values and becomes an important foundation for further training, development of Augmented Reality-based learning media, and strengthening ongoing cooperation between universities and Islamic boarding schools.